2021
DOI: 10.1021/acsearthspacechem.1c00083
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Computational Study on Fe2NiP Schreibersite: Bulk and Surface Characterization

Abstract: Phosphorous is ubiquitous in planet Earth and plays a fundamental role in all living systems. Finding a reasonable prebiotic source of phosphorous is not trivial, as common sources where it is present nowadays are in the form of phosphate minerals, which are rather insoluble and non-reactive materials, and, accordingly, unavailable for being readily incorporated in living organisms. A possible source of phosphorous is from the exogenous meteoritic bombardment and, in particular, in iron/nickel phosphites. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 69 publications
(137 reference statements)
3
19
0
Order By: Relevance
“…In laboratory investigations of the chemistry occurring within interstellar ices, however, ices are usually deposited onto flat surfaces used for transmission or reflection spectroscopy (e.g., gold, zinc selenide, magnesium fluoride, etc.). Although previous studies have acknowledged that adsorbent morphology may play an important role in the chemistry or spectroscopy of the adsorbate ice (Perets et al, 2007;Gull et al, 2015;Qasim et al, 2017;Wakelam et al, 2017;Pantaleone et al, 2021), there is a scarcity of studies that have considered this experimentally, and fewer still that have considered the chemical influence of the interaction of flat substrates with incident radiation. One study by Mason et al (2008) showed that the infrared spectrum of hexagonal crystalline water ice deposited over soot particles suspended in an ultrasonic trap differed somewhat to that of the same ice deposited onto flat fluoride substrates traditionally used in laboratory astrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory investigations of the chemistry occurring within interstellar ices, however, ices are usually deposited onto flat surfaces used for transmission or reflection spectroscopy (e.g., gold, zinc selenide, magnesium fluoride, etc.). Although previous studies have acknowledged that adsorbent morphology may play an important role in the chemistry or spectroscopy of the adsorbate ice (Perets et al, 2007;Gull et al, 2015;Qasim et al, 2017;Wakelam et al, 2017;Pantaleone et al, 2021), there is a scarcity of studies that have considered this experimentally, and fewer still that have considered the chemical influence of the interaction of flat substrates with incident radiation. One study by Mason et al (2008) showed that the infrared spectrum of hexagonal crystalline water ice deposited over soot particles suspended in an ultrasonic trap differed somewhat to that of the same ice deposited onto flat fluoride substrates traditionally used in laboratory astrochemistry.…”
Section: Introductionmentioning
confidence: 99%
“…To study the weathering process of schreibersite, the interaction of water was only modeled on the (110) most stable schreibersite surface, as characterized in our recent work. 23 The adsorption of water was simulated at different surface coverage regimes, from a single water molecule to the monolayer up to a thin liquid water multilayer.…”
Section: Resultsmentioning
confidence: 99%
“…This setup was chosen according to the best results obtained in our previous work on the bulk and bare surfaces of schreibersite. 23 On O and H atoms, the original D* parameters were used. This method of choice is referred to as PBE-D*0 along the work.…”
Section: Computational Detailsmentioning
confidence: 99%
“…The same approach was used to characterize the pristine schreibersite. 23 Geometry optimizations and frequency calculations were performed with the gradient corrected PBE functional, 32 with a posteriori Grimme D2 correction, 33 modified for solids (D*). 34 Moreover, C6 atomic coefficients related to polarizabilities on Fe and Ni metal atoms were set to 0 (i.e.…”
Section: -Computational Detailsmentioning
confidence: 99%
“…[20][21][22] A recent computational work on the bulk and surface structures and properties of schreibersite was published by us. 23 According to that, it is unlikely that the oxygen of H2O (partially negatively charged) interacts with the surface P atoms, which also bring a partial (close to -1e) negative charge, [23][24][25][26] thus resulting in an electrostatic repulsion. In the present paper we simulate the adsorption of water on the most stable facet of schreibersite, namely the {110} exploring different water's coverage regimes, up to a water multilayer.…”
Section: -Introductionmentioning
confidence: 99%